Effect of Structured Cardiac Rehabilitation on Quality of Life and Functional Recovery in Post-Coronary Artery Bypass Graft (CABG) Patients - Aamir Siddique, Shaoib Ahmed Zia, Muhammad Zahid Ali Raza, Tayyab Mohyuddin, Arslan Aslam Chahudhary, Faiza Altaf (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Coronary artery bypass grafting (CABG) is a widely performed surgical procedure for the treatment of advanced coronary artery disease (CAD). While it effectively relieves symptoms and improves survival, many patients experience prolonged physical, psychological, and functional impairments post-surgery. Structured cardiac rehabilitation (CR) has been recognized globally as a vital component of postoperative recovery; however, its implementation and evaluation in resource-constrained settings remain limited. Objective: To evaluate the impact of a 12-week structured cardiac rehabilitation program on quality of life and functional recovery among post-CABG patients. Methodology: This prospective observational study was included 79 patients (52 males, 27 females) aged 35–75 years who had recently undergone isolated CABG. Participants were enrolled within 3–4 weeks postoperatively and completed a structured CR program consisting of supervised exercise, dietary counseling, stress management, and education. Quality of life was assessed using the Short Form-36 Health Survey (SF-36), while functional capacity was measured through the 6-minute walk test (6MWT), both pre- and post-rehabilitation. Statistical analysis was conducted using paired sample t-tests. Results: Post-rehabilitation, significant improvements (p < 0.001) were observed in all SF-36 domains including physical functioning, vitality, social and emotional well-being, and mental health. The 6MWT distance increased from a mean of 298.4 ± 52.3 meters to 392.7 ± 46.8 meters, reflecting enhanced physical capacity. Conclusion: Structured CR significantly improves health-related quality of life and physical recovery in post-CABG patients. These findings support the routine integration of structured CR into postoperative care, especially in developing healthcare systems. Keywords: Coronary artery bypass grafting, Cardiac rehabilitation, Quality of life, Functional recovery, SF-36, 6-minute walk test, Postoperative care.